Extreme speech and democracy - Hare, Ivan.; Weinstein, James, 1953- (Oxford : Oxford University Press, 2009)
This title considers the constitutionality of hate speech regulation, and examines how liberal democracies have adopted fundamental differences in the way they respond to racist or extreme expressions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Freedom of speech; Hate speech